Prospective Study of Upper Gastro Intestinal Tract Endoscopy Finding and its Relation to Smoking in Baquba Teaching Hospital - Yaseen, Shukr Mahmood; Ahmed, Shahad Kareem (Diyala Journal of Medicine, 2019)
Background: The associations of smoking with endoscopic finding abnormalities were established especially in peptic ulcer that found of clear relation between smoking and peptic ulcer. Objective: The aims of this study were to understand the relation and association of ulcers with smoking, in addition to disorders finding like inflammations (esophagitis, doudenitis, gastritis), cancer and other cases . Patients and Methods: This study comprised of 1231 out patients admitted to Baquba teaching hospital in endoscopic finding unit of Baquba city-Iraq during the period between January 2014 to January 2015, 643 patients were males and 588 were females, ranging in age from 7 to 87 years, According to smoking habits, the patients were divided into three categories: non-smokers, current smokers, ex-smokers. The diagnostic endoscopic findings were concentrated only of the disorders lesions in GIT of ulcerations, inflammations, cancers, and other cases. In addition to normal findings who were established endoscopy without diagnoses of disorders. Results: The result showed increased of percentage (31.6%) of duodenal ulcer in male smokers and Gastritis in female (25.8%) of smokers. The frequency of duodenal, gastric ulcers and gastric cancer that showed high level in smoker's male ulcer and non-smokers female ulcer compared with another disorders value of smokers, non- smokers and ex-smokers. Duodenitis, gastritis, esophagitis was high percentage in female non- smokers recorded (p<0.05) between smokers with non-smokers. Gastric cancer showed high percentage in male smokers (n=7) and female non- smokers (n=7) recorded (p<0.05) between smokers with ex-smokers and non- smokers. Other cases, showed high percentage (n=69) in non-smokers Conclusion: Significance relationships between smoking with ulcer and gastritis, especially by duodenal ulcer in male smokers and gastritis in female smokers, the reasons is effecting of smoking.